Por Que Pensamento eNão Teoria ? A Imaginação Político-Social Brasileira e o Fantasma da Condição Periférica (1880-1970) - Christian Edward Cyril Lynch (Universidade do Estado do Rio de Janeiro, 2013)
Why do we refer to Brazilian political reflection as Thought rather than theory ? The hypothesis I intend to explore here is that inBrazil,the mainreasonforthe term thought to refer to the countrys intellectual products lies in the fact that the elites have always considered such products more or less inferior to those developed in Europe and the United States, due to their own more general perception of Brazils peripheral status. To frame this question, I will discuss the terminological issue of theory and thought in the field of political science. Next, I will examine h ow some leading Brazilian scholars assess the countrys place in the world and the quality of its intellectual products, especially those of a social and political nature. This analysis will be divided into two periods, the first pertaining to the predominance of the cosmopolitanculturalparadigmfromthelate19 th centurytothe1920s,andthe second with the nationalist cultural paradigm, lasting nearly until the late 20 th century.